EXPERIENCE WITH IMPACTED FOREIGN BODIES IN THE MAXILLOFACIAL REGION AT A NIGERIAN TEACHING HOSPITAL - Olusanya, AA (J West Afr Coll Surg, 2015)
BACKGROUND: The maxillofacial region has a complex anatomy and is replete with orifices and tissue dead spaces which could harbor foreign bodies. It is important to identify a foreign body impaction when it occurs, as it can be a source of persistent pain, infection and suppuration, it could also further migrate to adjacent regions of the body. The aim of this study is to report the clinical presentation, the prevalence, diagnosis, management and outcome of maxillofacial foreign body impaction in Ibadan, Nigeria. METHODOLOGY: This is a prospective clinic based epidemiological study carried out at the Department of Oral and Maxillofacial surgery, University College hospital, Ibadan, Nigeria. Data of all the patients presenting with foreign body impaction department from January 2008 to July 2013 were recorded into a proforma. The data which included demographics, type of foreign body impaction, predisposing factors, clinical presentation, diagnosis, treatment provided and outcome were analyzed using IBM SPSS version 19. RESULTS: A total of 5571 patients presented in the clinic during the study period with 16 of the patients presenting with foreign body impaction in the maxillofacial region prevalence rate of 0.29% There were 8 (50%) males and 8 (50%) females with male/female ratio of 1:1.The age ranged from .. to .. with a mean age of 21.89+/-17.047years. Iatrogenically displaced tooth 4 (25%) was the commonest foreign body impacted in the maxillofacial region while the submandibular region 3 (18.8%) was the commonest site. Majority 6 (40%) of the patients had retrieval of the foreign body under local anaesthesia. CONCLUSION: Foreign body impactions in the maxillofacial region are not common and are varied in nature. Their management is straightforward when they are impacted in an accessible and superficial site otherwise their diagnosis could be difficult and their management more challenging.